Manajemen Strategi Dalam Peningkatan Literasi Masyarakat Melalui Program Ayo Belajar - Tria Febri Lestari Tria; Indah Ayu Permana Pribadi; Zaula Rizqi Atika; Chamid Sutikno; Ariesta Amanda (Al-Abshar: Journal of Islamic Education Management, 2026)
The purpose of this study is to determine the strategic management of the Purbalingga Regency Archives and Library Office in improving community literacy through the Ayo Belajar di Perpustakaan (Ajar Pustaka) program. The method used is a qualitative method with a case study approach, while data collection techniques were carried out through observation, interviews, and documentation using purposive sampling techniques. Data analysis used the Miles and Huberman model, which includes data condensation, data presentation, and conclusion drawing. The research focus used Wheelen and Hunger's strategic management theory, namely environmental analysis, strategy formulation, strategy implementation, and evaluation and control. The results of the study show that the literacy improvement strategy through the Ajar Pustaka program has been implemented fairly well. At the environmental analysis stage, the agency has a clear organizational structure, adequate facilities and infrastructure, and extensive collaboration with schools and communities. Strategy formulation is conducted participatively through internal work meetings and is established through a Decree of the Head of the Agency as the basis for forming the program innovation team. Strategy implementation is realized through educational and participatory literacy activities such as storytelling, read-aloud sessions, writing training, discussions, and library services, which have contributed to an increase in visitor numbers and improvements in the Community Literacy Development Index (IPLM). Evaluation and control are carried out through periodic monitoring of performance achievements, although they are not yet supported by a specific Standard Operating Procedure (SOP) for the program.